Rol del padre de familia y su incidencia en el aprendizaje en los estudiantes de la Escuela Isidro Ayora, Ventanas. 2022 - Berruz Gordillo, Mariuxi Sulay (2023)
In the present work, the role of parents in the learning process of the students of the Isidro Ayora School was analyzed because it was detected that there was currently no effective participation on their part, reflecting this in the level of learning. of their children and their grades, an issue that was worrisome for the teachers of said institution. As a first point, the causes of the low school performance of the students were identified as a result of this analysis, it was evidenced that the scarce accompaniment of the parents in the tasks of their children influences both the grades and their motivation to study and this made the work difficult. of the teachers since there was no teamwork to ensure that the students reach the necessary knowledge. It is important to bear in mind that the acquisition of knowledge not only occurs in institutions, but it is the job of parents to be aware of their children's education and thus be able to resolve any doubts that arise along the way, all this in conjunction with the help of the teacher, therefore, having a good teacher-parent-student communication is essential to be successful.